Chaetotaxy of Neotropical Cyphoderus caetetus sp. nov. with comments on the taxonomic position of Cyphoderinae within Paronellidae (Collembola, Entomobryoidea) - Zeppelini, Douglas; Oliveira, João V.l.c. (Zootaxa, 2016)
The description of a new species, Cyphoderus caetetus sp. nov., led to comparisons among Paronellidae (Cyphoderinae and Paronellinae), which showed that the chaetotaxy of the first abdominal segment is very similar in Cyphoderus, Troglobius (Cyphoderinae) and Trogolaphysa (Paronellini), and much reduced in relation to that seen in Lepidonella (Paronellinae, Bromacanthini), Pseudosinella and Seira (Entomobryidae). This feature, along with the presence of pseudopores behind the posterior row of setae on the fourth abdominal segment as seen in Troglopedetes, Trogolaphysa and Cyphoderinae (absent in Lepidonella and Entomobryidae), suggests that Cyphoderinae is more closely related to tribe Paronellini than Paronellini is to Bromacanthini and Entomobryidae, and that the subfamily Paronellinae is paraphyletic if Cyphoderinae is excluded. We propose including Cyphoderini as the apical group in Paronellinae together with Paronellini (Trogolaphysa and Troglopedetes).